Development and Application of WC-Based Alloys Bonded with Alternative Binder Phase. Issue 3 (4th May 2019) - Sun, Jialin; Zhao, Jun; Gong, Feng; Ni, Xiuying; Li, Zuoli
Abstract: WC–Co alloys have enjoyed great practical significance owing to their excellent properties during the past decades. Despite the advantages, however, recently there have been concerns about the challenges associated with the use of Co, i.e. price instability (the major incentive for alternative binder development), toxicity and properties degeneration. Thus, the current study applies towards summarize the current knowledge of the impacts of different binders partial or total substitution of the traditional cobalt binder highlighting the influences of metal, intermetallic compound, ceramics (metal oxide) binders on the sintering behavior as well as mechanical properties of WC-based alloys, so as to provide reference for those who would like to enhance the performance of cemented carbides with better reliability advancing them to further wide applications and prepare the alloys in a way that is environment friendly, harmless to human health and low in production cost. It is concluded that the alternative for cobalt in tungsten carbide cemented carbide is economically and technically feasible. Strict control of the chemical composition of the binder coupled with taking into careful account the effects of sintering process and subsequent treatments is of great importance to improve the sintering behavior and tailor mechanical properties of tungsten carbide-based hardmetals.